Formulación de la cadena productiva del caracol en Cundinamarca y Boyacá – Colombia para exportar hacia el mercado español (2009)
To formulate the snail productive chain two referents, the European Union one, specifically, Spain, as well as the Colombian norms, regarding aspects as production and commercialization, were considered. The chain, to develop an offer of exportable products of alimentary use, to generate employment, income improvement for small and medium producers, as well as the achievement of devises, allowing to potentialize this agro-industrial activity, recently created in Colombia, is proposed. This research allowed to determine the opportunities of the snail export to the Spanish market and the Helicicola activity, having in mind the most relevant aspects of the chain, the companies, the associations as Fedecohel, the universities, the financial sector and furthermore the government. This, in order to develop coordinated activities and in the future, to supply, in a guaranteed manner, processed snail products or meat derived and sub-products, produced and commercialized in economies, at scale, in terms of production, volume, quality, logistic of physical distribution at national and international level, paking and terms of negotiation in the market that allow them to fulfil the international market. For this, the traditional system of production has to be transformed, to make it more productive and competitive and this way to allow the nascent companies to compete and access the international markets, especially the Spanish one.